Prognosis of cholangiocarcinoma patients based on multiple patterns of programmed cell death, integrated analysis of the immune microenvironment and drug sensitivity - Xu, Yupeng; Sun, Jian; Yan, Xin; Mao, Zhenliao; Chen, Yiming (Frontiers in Genetics, 2025)
BackgroundCholangiocarcinoma (CHOL) is a highly malignant bile duct cancer with a poor prognosis and rising incidence. Programmed cell death (PCD) plays a crucial role in cancer biology, influencing tumor immunity and treatment response. This study analyzes the impact of multiple PCD patterns on CHOL prognosis, tumor microenvironment (TME) and drug sensitivity.MethodsRNA sequencing data from TCGA-CHOL and GSE107943 were analyzed to identify PCD-related genes. A PCD-associated Risk Score was constructed using Cox and Lasso regression analyses. The score’s prognostic value was assessed through survival analysis, ROC curves, and functional annotation.ResultsWe identified 111 differentially expressed PCD-related genes, including NCK2, BNIP3 and BIK, that constituted PCD-associated Risk Score and correlated with prognosis of CHOL. Functional analyses indicated enrichment in immune-related processes. High-risk patients showed increased immune cell infiltration and higher immune checkpoint expression, suggesting a benefit from immunotherapy. They also demonstrated greater sensitivity to several chemotherapeutic and targeted agents.ConclusionPCD-associated Risk Score is a robust prognostic tool for CHOL, influencing TME modulation and therapeutic response, and may guide personalized treatment strategies.